Population dynamics parameters of Silver Pomfret Pampus argenteus in Iranian waters of the northern Persian Gulf and Oman Sea - MEHRAN PARSA; MAHSA MAHMOUDI KHOSHDAREHGI; ALI NEKURO; MOJTABA POULADI (Society for Indonesian Biodiversity, 2017)
Parsa M, Mahmoudi Khoshdarehgi M, Nekuro A, Pouladi M. 2017. Population dynamics parameters of Silver Pomfret Pampus argenteus in Iranian waters of the northern Persian Gulf and Oman Sea. Biodiversitas 18: 633-638. This research represents population dynamics parameters of Pampus argenteus including age, growth and mortality parameters in Iranian waters of the northern Persian Gulf and Oman Sea using length-frequency data. Fork length and total weight data collecting of P. argenteus were conducted from April 2014 to March 2015. A total of 1919 specimen were collected ranging from 10 to 32 cm fork length and 35 to 1075 g total weight. The mean length and weight were recorded to be 19.97±0.12 cm and 272.04±7.43 g, respectively. The relationship between fork length and total weight was determined as W = 0.0231FL3.141 (R2=0.9932, n= 643) and indicated that P. argenteus grew allometrically in the study region. The Von Bertalanffy growth function estimates were obtained as: L∞ = 32.55 cm, K = 0.3 year-1, t0=-0.54 years and ϕ′= 2.5. The infinite weight of P. argenteus was estimated as 1301.77 g. The annual instantaneous rate of total mortality (Z) was 1.55 year-1, the natural mortality (M) was 0.75 year-1 and the fishing mortality (F) was 0.78 year-1. Furthermore, the exploitation rate (E) was calculated as 0.51. Results of the obtained exploitation rate showed that P. argenteus was fully exploited in the study region.